POSITION OF WORKERS WITH DISABILITIES ACCORDING TO THE JURIDICAL REVIEW OF THE MANPOWER ACT AND THE EMPLOYMENT CREATION ACT - Nilam Hidayah; Imam Budi Santoso (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
This study discusses the rights of persons with disabilities to obtain decent work in order to maintain their lives. Regulations regarding disabled workers have been stated in the Manpower Act and the Job Creation Act. These two laws have not been fully understood and implemented by employers who employ disabled workers, as evidenced by the high number of cases of violations of the rights of disabled workers in various regions. Writing articles using normative juridical research related to researching secondary data and legislation, namely Law Number 13 of 2003 concerning Manpower and Law Number 11 of 2020 concerning Job Creation. The position of disabled workers has been regulated in the Manpower Act, this has met the level of sufficient regulatory policy. However, the emergence of the Employment Creation Law has created a disharmony between the rights or needs for respect and protection of workers with disabilities. The emergence of various cases of violations of the rights of workers with disabilities is a matter of great concern. The Manpower Act and the Job Creation Act have regulated this matter, but have not been able to maximize the protection of disabled workers.